Segmentacja rynków zagranicznych jako determinant konkurencyjności międzynarodowej przedsiębiorstwa - Sobczak, Elżbieta (Segmentation of foreign markets as a determinant of international competitiveness of an enterpris, 2005)
The study provides an analysis of the influence of foreign markets’ segmentation on international competitiveness of an enterprise. The concept of both international competitiveness and markets’ segmentation has been defined. The problems of segmentation strategy and segmentation research effectiveness have also been touched upon.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 130-138